(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Mange or scabies in cats, caused by Notoedres cati and Sarcoptes scabiei, is a highly contagious parasitic skin disease. Research efforts have been intensified in both developed and developing countries to evaluate the use of clinical and scientifically validated herbal drugs on humans and also animals. This study aimed to evaluate the therapeutic efficacy of black ginger (Kaempferia parviflora) paste against mange in stray cats naturally infested with N. cati. Twelve cats exhibiting clinical signs of mange were captured in Kota Bharu, Kelantan, and housed in isolation. Infestation was confirmed via deep skin scrapings, and lesion severity scores were recorded before treatment. Cats were randomly assigned to four treatment groups (n=3 per group). Results indicated that a higher concentration of black ginger paste (0.7 g/ml) demonstrated superior efficacy compared to a lower concentration (0.5 g/ml). However, no significant differences (P-value = 0.105) were observed among the four treatment groups (extra virgin coconut oil, 0.5 and 0.7 g/ml black ginger pastes, and ivermectin). No viable mites were revealed from cats treated with the paste and with a concentration of 0.7 g/ml. Black ginger paste in this concentration was able to achieve an efficacy percentage of almost 30% of Notoedres-induced skin lesion score reduction. These preliminary findings suggest that K. parviflora may offer a promising plant-based alternative for managing notoedric mange in cats, pending further confirmatory studies with larger sample sizes.